The witness of Matthew and Mark to Christ - Stonehouse, Ned Bernard, 1902-1962 (London, UK Tyndale, 1944)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. Matthew -- criticism, interpretation, etc; Bible. N.T. Mark -- criticism, interpretation, etc